Ecological Momentary Assessment of Self-Attitudes in Response to Dietary Lapses - Schumacher, Leah M. (Health Psychol, 2017)
OBJECTIVE: To examine whether self-attitudes and self-efficacy after dietary lapses relate to lapse frequency or predict risk for lapsing again on the same day. METHODS: Adults with overweight/obesity (n = 91) completed ecological momentary assessment for 14 days at the start of a lifestyle modification program. At each survey, participants reported whether they had experienced a dietary lapse, and, if so, reported their self-attitudes (i.e., self-criticism, self-forgiveness, self-regard) and self-efficacy. The relationships between participants’ typical (i.e., average level for each participant across lapses) self-attitudes/self-efficacy after lapsing and lapse frequency were examined using correlations. Generalized estimating equations examined whether participants’ typical (average across lapses; between-person effect) self-attitudes/self-efficacy or momentary (i.e., level of each variable at a particular lapse relative to one’s typical level; within-person effect) self-attitudes/self-efficacy predicted same-day lapse occurrence. RESULTS: Lower typical self-efficacy and more negative typical self-regard related to greater lapse frequency. Additionally, lower momentary self-criticism predicted greater likelihood of same-day lapse occurrence. There also was a quadratic relationship between typical self-regard and risk of same-day lapse occurrence, such that individuals with either more negative or more positive typical self-regard were more likely to lapse on the same day. CONCLUSIONS: Findings provide preliminary support for the relevance of self-attitudes and self-efficacy to lapses during early lifestyle modification. While greater typical self-efficacy and more positive typical self-regard are associated with fewer lapses, lower momentary self-criticism and very positive or negative typical self-regard may confer risk for same-day lapses.